BIOGRAFIA MUSEOLÓGICO-CURATORIAL DE UMA COLEÇÃO ARQUEOLÓGICA: O CASO DO MUSEU DA CIDADE DO RIO GRANDE (MCRG), RS, BRASIL. - Pereira Da Costa, Matheus; Lemos Ribeiro, Diego; Soares Poloni, Rita Juliana (Museologia e Patrimônio, 2022)
The following article aims to present the biographical trajectory of an archeological collection, which is on long-term exhibition at the Museu da Cidade do Rio Grande, RS, Brazil. The chronology established for analysis is between the years 1984 to 2020, and refers to the scenographic and discursive changes that took place in the institution. The methodological assumptions are based on the survey of primary sources related to the documentation of the formation of the institutional collection, and secondary ones based on the participant observation strategy and the realization of semi-structured interviews that were applied with the research interlocutors. The results obtained point to a unique biographical trajectory still in process, which made it possible to archeologically connect different times, events, institutions and people. Finally, some considerations are made about the importance of the social and symbolic appropriation of the archaeological heritage in museums, with a view to generating new institutional qualifications and social (re)significations of these findings in the present.